Benefit of Childbirth Care Counseling for Mood of Postpartum Period (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Postpartum mood disorder experienced by mothers was characterized by severe fatigue, poor concentration, tiredness, sadness, and anger at her husband. This postpartum mood disorders could progress to postpartum depression and postpartum psychosis. Childbirth care counseling was an attempt to allow mothers to adapt to her postpartum condition. The objective of this research was to identify the effect of childbirth care counseling on postpartum mood changes at Wates General Hospital, Kulonprogo. This research used pre-experimental design with post test. We used purposive sampling to obtain 20 respondents in the experimental group and 20 respondents in the control group. Moreover, EPDS instruments were also used in this research. Saphiro-Wilk normality test resulted in SD=0.0000.05. The Mann-Whitney test resulted Z-2.054t-table, Î±=0.0400.05. We found that there was a significant benefit of childbirth care counseling on postpartum mood changes at Wates General Hospital, Kulonprogo. The significance of this research is that health workers in prenatal units should provide counseling about postpartum care to mothers in their third trimester.